2019
DOI: 10.33010/recie.v4i2.431
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de las Nuevas Tecnologías en el aprendizaje del Baile Flamenco

Abstract: En las últimas décadas el avance de las Nuevas Tecnologías ha propiciado un cambio en los procesos de aprendizaje del baile flamenco. Esto es debido a su carácter efímero que, como modalidad de danza, precisa de los medios audiovisuales para poder ser conservado en el tiempo. El desarrollo de plataformas como You tube o Facebook han contribuido al acceso inmediato de vídeos en cualquier parte del mundo, lo que ha beneficiado al alumnado tanto español como extranjero. Como consecuencia, ha proliferado la oferta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Educational research is sorely needed to adapt this art to the new paradigms of education. Bárbara de las Heras [7] looked at the current transformation of teaching systems and methods in flamenco dance through a comparative study of three generations of teachers and dancers and concluded that a quantitative and qualitative leap had taken place between the second and third generations in terms of teaching techniques, style, organisation and duration of classes, learning processes and other parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Educational research is sorely needed to adapt this art to the new paradigms of education. Bárbara de las Heras [7] looked at the current transformation of teaching systems and methods in flamenco dance through a comparative study of three generations of teachers and dancers and concluded that a quantitative and qualitative leap had taken place between the second and third generations in terms of teaching techniques, style, organisation and duration of classes, learning processes and other parameters.…”
Section: Introductionmentioning
confidence: 99%